2020
DOI: 10.1002/pssa.202000237
|View full text |Cite
|
Sign up to set email alerts
|

Single Ion Implantation of Bismuth

Abstract: Herein, the results from a focused ion beam instrument, designed to implant single ions with a view to the fabrication of qubits for quantum technologies, are presented. The difficulty of single ion implantation is accurately counting the ion impacts. This is achieved here through the detection of secondary electrons generated upon each ion impact. The implantation of single bismuth ions with different charge states into Si, Ge, Cu, and Au substrates is reported, and the counting detection efficiency for singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…2), and even recovery times that are comparable with the inverse of the typical microwave spin qubit Larmor frequencies (e.g., X-band at 10 GHz), and much faster than consequent Bloch rotation times [36][37][38][39][40] . For concreteness we give a specific example for Si:Bi, a popular qubit choice [44][45][46] , which displays large zero-field spin splitting (originating from hyperfine interaction) visible in the small-signal absorption shown on Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
“…2), and even recovery times that are comparable with the inverse of the typical microwave spin qubit Larmor frequencies (e.g., X-band at 10 GHz), and much faster than consequent Bloch rotation times [36][37][38][39][40] . For concreteness we give a specific example for Si:Bi, a popular qubit choice [44][45][46] , which displays large zero-field spin splitting (originating from hyperfine interaction) visible in the small-signal absorption shown on Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative method for determining η is to collect the number of negatives m for a fixed, large number of pulses, m , and then use p=m/m and Equation (12), as in Cassidy et al [ 18 ] It may be shown that for small λ , ση2=σλ2/λ2+1/mλ. Note that just as for the stopping time experiment in the previous paragraph, small λ is not beneficial for such calibration experiments, and ideally mλ/σλ2 just as before, so there is no statistical advantage in either experiment.…”
Section: Experimental Calibration Of the Detector Efficiency And Its Experimental Uncertaintymentioning
confidence: 99%
“…Note that just as for the stopping time experiment in the previous paragraph, small λ is not beneficial for such calibration experiments, and ideally mλ/σλ2 just as before, so there is no statistical advantage in either experiment. See Cassidy et al [ 18 ] for a treatment of the uncertainty in η if it is determined from a graph of ln(m/m) versus λ rather than a single setting of λ . Other experimenters [ 11 ] have investigated the number of positives as a proportion of the number of pulses containing ions, and this fraction has been called the detection efficiency, Pnormald.…”
Section: Experimental Calibration Of the Detector Efficiency And Its Experimental Uncertaintymentioning
confidence: 99%
See 2 more Smart Citations